Evaluation of Levenberg–Marquardt neural networks and stacked autoencoders clustering for skin lesion analysis, screening and follow‐up. Issue 7 (24th August 2018) - Rundo, Francesco; Conoci, Sabrina; Banna, Giuseppe L.; Ortis, Alessandro; Stanco, Filippo; Battiato, Sebastiano
Abstract : Traditional methods for early detection of melanoma rely on the visual analysis of the skin lesions performed by a dermatologist. The analysis is based on the so‐called ABCDE (Asymmetry, Border irregularity, Colour variegation, Diameter, Evolution) criteria, although confirmation is obtained through biopsy performed by a pathologist. The proposed method exploits an automatic pipeline based on morphological analysis and evaluation of skin lesion dermoscopy images. Preliminary segmentation and pre‐processing of dermoscopy image by SC‐cellular neural networks is performed, in order to obtain ad‐hoc grey‐level skin lesion image that is further exploited to extract analytic innovative hand‐crafted image features for oncological risks assessment. In the end, a pre‐trained Levenberg–Marquardt neural network is used to perform ad‐hoc clustering of such features in order to achieve an efficient nevus discrimination (benign against melanoma), as well as a numerical array to be used for follow‐up rate definition and assessment. Moreover, the authors further evaluated a combination of stacked autoencoders in lieu of the Levenberg–Marquardt neural network for the clustering step.